Evaluation of Some Serum Biochemical Indices in Patients with Gestational Diabetes - A. Hadi, Marwa; H. Al-Hashimi, Nawal (Al-Nahrain Journal of Science, 2023)
The aim of this study was to evaluate some serum biochemical indices in patients with gestational diabetes. Among the study’s participants were 100 expectant mothers ranging in age from 24 to 35 who had been diagnosed with diabetes at a maternity hospital or pregnancy center in Baghdad city. According to their previous menstrual cycle or an ultrasound, these ladies were between 28 and 33 weeks pregnant. There were two categories of pregnant women: Twenty pregnant women in good health comprised (control group). Eighty GDM-pregnant women were enrolled. The current results showed a significant increase in levels of glucose, cholesterol, triglyceride, ALT, bilirubin, uric acid, and creatinine in the GDM group as compared with control patients, also a significant decrease in the levels of Albumin, HDL in GDM group as compared with control group. There were no significant differences in the levels of urea and AST in both GDM and control groups. In conclusion, there was a significant increase in levels of glucose, cholesterol, triglyceride, ALT, bilirubin, uric acid, and creatinine in the GDM group.